Mutation of PAX3 and MITF genes in a family with type 1 Waardenburg syndrome: a case series (Medical Journal of Indonesia, 2023)
Waardenburg syndrome (WS) is a rare genetical disorder, characterized with pigmentary abnormalities of the eyes, skin, hair, dystopia canthorum, and sensorineural deafness. In Majene, West Sulawesi, 12 members of a 4-generation family presented manifestations of WS. We examined the presence of mutations in 5 family members with type 1 WS and the other 5 normal phenotype family members to identify mutations of PAX3 and MITF genes. Ophthalmic examination and peripheral blood test were done. Conventional polymerase chain reaction and direct Sanger sequencing were then performed to detect the mutation. 26 mutations of PAX3 gene were only identified in patients with major and minor criteria, including 7 missense mutations (substitutions) and 2 insertions in exons 1, 2, and 6, as well as 17 intronic changes in intron 8. No mutations were detected in MITF gene.